2015
DOI: 10.17116/neiro20157965-14
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between diffusion kurtosis imaging and the proliferative activity of brain glioma

Abstract: DKI has good capabilities to detect immunohistochemical changes in gliomas. DKI demonstrated a high sensitivity in detection of microstructural changes in the contralateral normal appearing white matter in patients with brain gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Beppu et al (26) observed a positive correlation between FA and tumor cell density, while Zhao et al (27) reported that MD was negatively correlated with Ki67, which is well known as an index of tumor cell proliferation. Similar evidence also indicates that tumor cell density, which depends on proliferative activity, is positively correlated with FA, but negatively correlated with MD (28,29). Of the different tumor types, an aggressive glioma would be expected to lead to reduced cell organization and higher cell density, thereby restricting water molecule diffusion and further increasing FA but decreasing MD.…”
Section: Discussionmentioning
confidence: 69%
“…Beppu et al (26) observed a positive correlation between FA and tumor cell density, while Zhao et al (27) reported that MD was negatively correlated with Ki67, which is well known as an index of tumor cell proliferation. Similar evidence also indicates that tumor cell density, which depends on proliferative activity, is positively correlated with FA, but negatively correlated with MD (28,29). Of the different tumor types, an aggressive glioma would be expected to lead to reduced cell organization and higher cell density, thereby restricting water molecule diffusion and further increasing FA but decreasing MD.…”
Section: Discussionmentioning
confidence: 69%
“…According to the DK-MRI results, diffusion kurtosis has a good chance to be more sensitive to early pathological changes in brain tissue in comparison with other diffusion parameters, in particular for predicting motor disorders after stroke [1,5,6]. It was noted that diffusion kurtosis characteristics depend on age, therefore, some factors should be taken into account when studying changes in these parameters during the pathological processes [2,3].…”
Section: Methodsmentioning
confidence: 99%
“…Индекс Ki-67/MIB-1 (Ki-67/MIB-1 LI) -отношение Ki-67-позитивных клеток, то есть находящихся в стадии пролиферации, ко всем клеткам опухоли [13]. Этот показатель является наиболее достоверным и самым распространенным методом оценки митотической активности, коррелирует с клиническим течением опухоли мозга.…”
Section: клинический случайunclassified